2.4GHz 대역에서의 응용을 위한 광대역 RF모듈 설계 및 제작 - 양두영; 강봉수; Yang Doo-Yeong; Kang Bong-Soo (한국콘텐츠학회 논문지, 6(4), 2006)
In this paper, a broadband RF module is designed and tested for 2.4GHz band applications. The RF module is composed of a low noise amplifier (LNA) with a three stage amplifier, a single ended gate mixer, matching circuits, a hairpin line band pass filter and a Chebyshev low pass filter to convert the radio frequency (RF) into the intermediate frequency (IF). The LNA has a high gain and stability, and the single ended gate mixer has a high conversion gain and wide dynamic range. In the analysis of the broadband RF module, the composite harmonic balance technique is used to analyze the operating characteristics of an RF module circuit. The RF module has a 55.2dB conversion gain with a 1.54dB low noise figure, $-120{\sim}-60dBm$ wide RF power dynamic range, -60dBm low harmonic spectrum and a good isolation factor among the RF, IF, and local oscillator (LO) ports. 본 논문에서는 2.4GHz 대역에서의 응용을 위한 광대역 RF 모들을 설계하고 제작하였다. 무선 주파 신호를 중간 주파수로 변환하기 위한 RF 모듈은 3단 증폭기로 이루어진 저잡음 증폭기(LNA), 단종단 게이트 믹서, 정합 회로, 헤어핀 라인 대역 통과 필터, 쳬비셰프 저역 통과 필터로 구성하였다. 저잡음 증폭기는 높은 이득과 안정도를 갖도록 설계하였으며, 단종단 게이트 믹서는 높은 변환이득과 넓은 동작 영역을 갖도록 설계하였다. 광대역 RF모듈의 해석에서는 복합화된 하모닉 밸런스드 기법을 사용하여 RF모듈의 동작 특성을 해석하였다. 설계된 RF 모듈은 55.2dB의 변환이득, 1.54dB의 낮은 잡음 특성, $-120{\sim}-60dBm$의 넓은 RF전력 동작 영역, -60dBm의 낮은 고조파 성분 그리고 RF, IF, LO포트 간에 우수한 분리 특성을 갖는다.